Self-actualization of families with a cerebrovascular disease patient by nurses, and of self-actualization of nurses themselves: an integrative review based on family care/caring theory - Hiroko Ota; Naohiro Hohashi (BMC Nursing)
Abstract Background and purpose When caring for patients hospitalized with cerebrovascular disease, a caring phenomenon occurs between the patient’s family and the nurse, and according to Hohashi’s Family Care/Caring Theory, the family and the nurse achieve self-actualization. However, the contents of self-actualization through specific care/caring are unclear. The purpose of this integrative review was to clarify the self-actualization of the nurse as an outcome of family care/caring, and the self-actualization of other individuals (that is, the family) who are supported by nurses. Methods A search conducted on 23rd December, 2023, using Ichushi-Web, CiNii and J-STAGE, which are extensive Japanese literature databases, identified 1,061 original articles using the keywords “cerebrovascular disease AND nurse.” The quality of the articles was assessed according to the Joanna Briggs Institute critical appraisal checklists. We conducted an integrative review of 11 articles describing transactions between nurses and families according to Toronto and Remington. Self-actualization of the nurse and self-actualization of other individuals were classified as subcategories and then as categories. Exclusion criteria included no description of family members, no practice by nurses, and not patients with cerebrovascular disease. Results Of the 11 studies utilized, 10 were qualitative studies and one was a quantitative descriptive study. Eight categories were identified for self-actualization of families with a cerebrovascular patient by nurses, including “Families can realize their hopes through the provision of an environment by nurses.” Three categories of self-actualization of the nurse were identified, including “Nurses can obtain a sense of satisfaction from the family.” Conclusion During the recovery process after hospitalization for cerebrovascular disease, a caring phenomenon occurs between the patient’s family and nurses, which can be understood using Family Care/Caring Theory. The family’s self-actualization and the nurse’s self-actualization were achieved through reciprocal concern between the two.